Importance of ice elasticity in simulating tide-induced grounding line variations along prograde bed slopes - N. Ross; P. Milillo; P. Milillo; P. Milillo; K. Nakshatrala; R. Ballarini; A. Stubblefield; L. Dini (The Cryosphere)
The grounding line, delineating the boundary where a grounded glacier becomes afloat in ocean water, shifts in response to tidal cycles. Here, we analyze COSMO-SkyMed Differential Interferometric Synthetic Aperture Radar (DInSAR) data acquired in 2020 and 2021 over Totten, Moscow University, and Rennick glaciers in East Antarctica, detecting tide-induced grounding line position variations from 0.5 to 12.5 km along prograde slopes ranging from ∼ 0 % to 5 %. Considering a glacier as a non-Newtonian fluid, we provide two-dimensional formulations of viscous and viscoelastic short-term behavior of a glacier while in partial frictional contact with the bedrock and while partially floating on seawater. Since the models' equations are not amenable to analytical treatment, numerical solutions are obtained using FEniCS, an open-source Python package for solving partial differential equations using the finite element method. We establish the dependence of the grounding zone width on glacier thickness, bed slope, and glacier flow speed and find that grounding zone predictions using a viscoelastic model significantly outperform those of a purely viscous model. This study underscores the critical role played by ice elasticity in continuum-mechanics-based glacier models on daily timescales and demonstrates how these models can be validated using DInSAR measurements.